2017
DOI: 10.1002/ccd.26965
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic postconditioning during primary percutaneous coronary intervention

Abstract: IPoC does not appear to reduce the risk of clinical adverse events in patients with ST-elevation myocardial infarction undergoing primary PCI. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Although hyperlipidemia was not associated with MVO in the current study, a prior meta-analysis found that statin use prior to primary PCI was associated with a lower risk of no-reflow (15). Additional approaches such as aspiration thrombectomy, deferred stenting strategy, and ischemic pre-conditioning have been shown to reduce the risk of noreflow; however, the improvement in angiographic measures with these strategies did not translate into improvement in clinical outcomes (16)(17)(18). In a patient level meta-analysis of three large RCTs, aspiration thrombectomy was associated with a trend towards reduced cardiovascular mortality in STEMI patients with high thrombus burden (19).…”
mentioning
confidence: 99%
“…Although hyperlipidemia was not associated with MVO in the current study, a prior meta-analysis found that statin use prior to primary PCI was associated with a lower risk of no-reflow (15). Additional approaches such as aspiration thrombectomy, deferred stenting strategy, and ischemic pre-conditioning have been shown to reduce the risk of noreflow; however, the improvement in angiographic measures with these strategies did not translate into improvement in clinical outcomes (16)(17)(18). In a patient level meta-analysis of three large RCTs, aspiration thrombectomy was associated with a trend towards reduced cardiovascular mortality in STEMI patients with high thrombus burden (19).…”
mentioning
confidence: 99%
“…On the wave of these pre-clinical findings, the largest IPoC trial in STEMI patients so far, the recent Third Danish Study of Optimal Acute Treatment of Patients With ST-elevation Myocardial Infarction-Ischemic Postconditioning (DANAMI-3-iPOST), failed to demonstrate that routine IPoC reduces the composite endpoint of all-cause death and hospitalization for heart failure at a median follow-up of about 3 years [ 2 ]. These results have been confirmed by a recent meta-analysis of randomized controlled trials investigating the usefulness of IPoC in STEMI patients undergoing primary PCI [ 3 ]. Other studies focused on some cytoprotective agents such as delcasertib: it is an antagonist of an isoenzyme of protein kinase C (PKC) involved in myocardial cell damage following ischemia.…”
mentioning
confidence: 55%
“…Given the lack of tangible clinical benefit with IPoC in the DANAMI‐3‐iPOST trial and in this comprehensive meta‐analysis, we could conclude that IPoC should not be performed in primary PCI for STEMI . However, the apparent discordance between the benefit of IPoC in terms of several surrogate endpoints and the lack of benefit in terms hard clinical endpoints provides an important discussion point.…”
mentioning
confidence: 86%
“…With this background in mind, in the current issue of the Journal, Mentias et al report the results of a well‐performed comprehensive meta‐analysis of randomized controlled trials investigating the usefulness of IPoC in patients with STEMI undergoing primary PCI . A total of 26 trials with 4,083 patients were included.…”
mentioning
confidence: 99%